(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2023)
The experiment consisted of two different strategies of pollination treatment on buckwheat (Fagopyrum esculentum) flowers, viz. T1=without netting and T2= netting. Pair plot technique was adopted to layout the present experiment with 12 replications. The most abundant species were identified as Apis cerana F. (9.28±2.62) from Hymenoptera and Menocheilus sexmaculatus (8.36±1.05) from Coleoptera foraging the field at 11 A. M., while Syrphus sp. (2.53±1.1) found as dominant species from Diptera order visited the field early in the morning (7 A. M.). Apis cerena and Apis mellifera were found to stay more time on buckwheat flowers. The highest 1000-seed weight (18.39 g) of buckwheat was recorded from the plot without netting (T1), whereas the lowest 1000-seed weight (9.17 g) was recorded from the plot with netting (T2). The highest seed yield per plant of buckwheat was recorded 22.68 g when the plot was without netting (T1) and the lowest was recorded 12.35 g when the plot was netted (T2). The highest yield per plot was recorded (0.8258 kg) when the field was opened for pollinators (T1) and the lowest yield per plot was recorded (0.399 kg) when the field was netted (T2). J. Biodivers. Conserv. Bioresour. Manag. 2023, 9(1): 109-118